Cardiac Strain between Normal Weight and Overweight Workers in Hot/Humid Weather in the Persian Gulf - Dehghan, Habibollah (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: In hot weather, overweight and obesity are considered as significant risk factors for the incidence of cardiac strain in workers. This study was aimed to compare cardiac strain among overweight and normal-weight workers in hot, humid conditions in the south of Iran. METHODS: This cross-sectional study was conducted on 71 workers in the south of Iran in summer 2010. The heart rate was measured at rest and at actual work. Cardiac strain based on working heart rate (WHR), the relative cardiac cost (RCC), the net cardiac cost (NCC), load relative cardiovascular (CVL), and heart rate reduction was analyzed in 35 normal-weight people (body mass index (BMI) <25 kg/m(2)) and 36 overweight people (BMI >25 kg/m(2)) using descriptive statistics. RESULTS: In 42% of the total workers, BMI was >25 kg/m(2). The average of Wet Bulb Globe Temperature Index (WBGT Index) in the two groups was not significantly different. The mean WHR in the two groups was 101 ± 20.3 and 112 ± 18.9, respectively (P = 0.026). Percentages exceeded the acceptable limits in the parameters NCC, RCC, WHR, CVL, and Brouha index, which were significantly higher in overweight people than in those with normal weight. CONCLUSIONS: Based on the study results, it is concluded that the severity of cardiac strain was higher in overweight workers compared with that in normal weight workers. Hence, in order to decrease the cardiac strain, selecting overweight individuals for these jobs should be avoided and also some vital intervention for losing weight should be implemented such as nutrition education and encouraging them regarding physical activity.